Adverse Effects of Carbetocin versus Oxytocin in the Prevention of Postpartum Haemorrhage after Caesarean Section: A Randomized Controlled Trial - D. Mannaerts; L. Van der Veeken; H. Coppejans; Y. Jacquemyn (Journal of Pregnancy)
Purpose. To compare the incidence of nausea, vomiting, and arterial hypotension between carbetocin and oxytocin to prevent haemorrhage after caesarean section (CS). Methods. A randomized controlled trial in term pregnant women undergoing planned CS. Groups were randomized to carbetocin or oxytocin. Blood pressure (BP), heart rate, presence of nausea/vomitus, and need for vasopressors were evaluated throughout surgery. Preoperative and postoperative haemoglobin and haematocrit levels were compared. Results. Fifty-eight women were randomized (carbetocin n=32; oxytocin n=26). Both medications had hypotensive effect, difference in BP for carbetocin versus oxytocin: systolic (14.4 ± 2.4 mmHg versus 8.5 ± 1.8 mmHg); diastolic (7.8 ± 1.6 mmHg versus 8.9 ± 3.0 mmHg) without significant difference between the drugs (p=0.1 and p=0.7). Both groups had similar needs for vasopressors. The presence of nausea was not rare, but the difference was not statistically significant (p=0.4). Average blood loss was slightly lower in the carbetocin group but not statistically significant (p=0.8). Conclusion. In planned CS, a possible clinical significant lower incidence of nausea after carbetocin was noted but this was not statistically significant. There were no differences regarding BP, heart rate, the need for vasopressor, and blood loss. The study was registered in the International Journal of Clinical Trials (ISRCTN 95504420, 2/2017).